HUBUNGAN BEBAN KERJA, IKLIM KERJA, DAN POSTUR KERJA TERHADAP KELUHAN MUSCULOSKELETAL PADA PEKERJA BAGGAGE HANDLING SERVICE BANDARA (Studi Kasus di Kokapura, Bandara Internasional Ahmad Yani Semarang) - Ayu Nidaan Khofiyya; Ari Suwondo; Siswi Jayanti (Jurnal Kesehatan Masyarakat, 2019)
Musculoskeletal Disorders are accumulations of injuries and pain that occur in the musculoskeletal system which are characterized by injuries to muscles, tendons, cartilages, ligaments, skeletons, vascular system, and nerves. Factors causing MSDs include work factors including work posture, workload, work duration, frequency, repetitive motion, while environmental factors include work climate, vibration, and lighting. The purpose of this study was to analyze the relationship between workload, work climate, work posture with musculoskeletal disorders on baggage handling service workers at the airport. This type of research is an analytical analytic study using cross-sectional studies. The population in this study were 54 baggage handling service workers at Kokapura Ahmad Yani International Airport Semarang with a sample of 36 people. The instrument of this study was the Nordic Body Map questionnaire to determine musculoskeletal disorders. The results showed there was a relationship between work posture (r-value = 0.001) and work climate (r-value = 0.019) with musculoskeletal disorders. Efforts to reduce and prevent musculoskeletal disorders on baggage handling service workers should managers provide socialization related to work ergonomics, scheduled heating activities before work and during work breaks.